Pathophysiology of Atherosclerosis Formation in Autoimmune Diseases: Rheumatoid Arthritis, Systemic Lupus Erythematosus, Primary Sjögren’s Syndrome, and Antiphospholipid Syndrome - Dwi Aryasatya Pranaja; Anita Liliana Susanti; Andri A. Rusman (Health & Medical Sciences, 2025)
This study aimed to systematically examine the autoimmune mechanisms contributing to atherosclerosis development in patients with Rheumatoid Arthritis, Systemic Lupus Erythematosus, Sjögren’s syndrome, and Antiphospholipid Syndrome. The focus was on identifying immunological pathways, inflammatory mediators, and vascular changes that accelerate atherosclerosis in these autoimmune conditions. A systematic scoping review was conducted following established scoping review guidelines. Peer-reviewed studies on immune-mediated processes, endothelial dysfunction, lipid changes, or cardiovascular outcomes in autoimmune diseases were sourced from PubMed, Scopus, and Web of Science, screened via electronic searches and predefined inclusion criteria. Data extraction focused on immune cell involvement, cytokine profiles, mechanisms of vascular injury, and indicators of atherosclerotic progression.The results demonstrated that chronic systemic inflammation is a central mechanism driving accelerated atherosclerosis in autoimmune diseases. Activated immune cells, particularly monocytes, macrophages, and T lymphocytes, were consistently reported to infiltrate the vascular endothelium, promoting endothelial dysfunction and intimal thickening. Pro-inflammatory cytokines such as tumor necrosis factor-alpha and interferon-gamma were frequently associated with increased expression of adhesion molecules, oxidative stress, and foam cell formation. Altered lipid metabolism, including increased levels of oxidized low-density lipoprotein, further contributed to plaque development. In Antiphospholipid Syndrome, autoantibody-mediated endothelial injury and thrombogenic processes were prominent, while immune complex deposition and complement activation were key contributors in Systemic Lupus Erythematosus. Overall, the findings indicate that immune dysregulation and persistent inflammation substantially increase cardiovascular risk in patients with autoimmune diseases, underscoring the need for targeted anti-inflammatory and immunomodulatory strategies to reduce atherosclerotic burden